2020
DOI: 10.1158/1078-0432.ccr-19-3890
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage HIF-1α Is an Independent Prognostic Indicator in Kidney Cancer

Abstract: Purpose: Clear cell renal cell carcinoma (ccRCC) is frequently associated with inactivation of the von Hippel-Lindau tumor suppressor, resulting in activation of HIF-1a and HIF-2a. The current paradigm, established using mechanistic cell-based studies, supports a tumor promoting role for HIF-2a, and a tumor suppressor role for HIF-1a. However, few studies have comprehensively examined the clinical relevance of this paradigm. Furthermore, the hypoxia-associated factor (HAF), which regulates the HIFs, has not be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…Some studies have shown that the number of TAMs infiltrating tissue is closely related to the vascular density in tumors. 120 , 121 Large aggregates of TAMs were found in anoxic areas, especially in necrotic tissues. 122 TAMs are regarded as significant producers of proangiogenic factors in malignant tumors because they release IL-1β, VEGF, TNF-α, and other cytokines.…”
Section: Macrophage-derived Exosomes Are Involved In Tumor Progressiomentioning
confidence: 99%
“…Some studies have shown that the number of TAMs infiltrating tissue is closely related to the vascular density in tumors. 120 , 121 Large aggregates of TAMs were found in anoxic areas, especially in necrotic tissues. 122 TAMs are regarded as significant producers of proangiogenic factors in malignant tumors because they release IL-1β, VEGF, TNF-α, and other cytokines.…”
Section: Macrophage-derived Exosomes Are Involved In Tumor Progressiomentioning
confidence: 99%
“…Tumor-associated macrophages (TAM) activate oncogenic signaling and facilitate tumor growth and progression by secreting cytokines, growth factors, and angiogenic mediators, as well as a variety of proteases that activate additional growth factors and angiogenic mediators embedded in the extracellular matrix [7][8][9][10][11][12][13][14] . These paracrine interactions are concentration-gradient-dependent, and as such, the underlying biology may be better reflected by measures of local cellular clustering as opposed to global density metrics.…”
Section: Introductionmentioning
confidence: 99%
“…These paracrine interactions are concentration-gradient-dependent, and as such, the underlying biology may be better reflected by measures of local cellular clustering as opposed to global density metrics. Prior work has demonstrated an association between TAM density and worse overall survival (OS) in patients with clear cell renal cell carcinoma (ccRCC), but none have assessed TAM cellular clustering 9,12,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that overexpression of cytoplasmic HIF1α is associated with a higher nuclear grade, larger tumor size, higher stage and shorter survival, while nuclear HIF1α overexpression is associated with better diagnostic parameters (i.e., lower nuclear grade, smaller tumor size and longer survival) [ 73 ]. However, a recent comprehensive study revealed that macrophage HIF1α appears to be an independent prognostic indicator for ccRCC [ 74 ]. These authors used a large cohort of ccRCC tumor tissues (380 on a tissue microarray, an additional 57 ccRCC from patients treated with antiangiogenic therapy for response associations analysis) to assess the expression of HAF (hypoxia-associated factor, which regulates HIFs), HIF1α and HIF2α in ccRCC.…”
Section: Hif1α and Hif2αmentioning
confidence: 99%
“…These authors used a large cohort of ccRCC tumor tissues (380 on a tissue microarray, an additional 57 ccRCC from patients treated with antiangiogenic therapy for response associations analysis) to assess the expression of HAF (hypoxia-associated factor, which regulates HIFs), HIF1α and HIF2α in ccRCC. The study revealed that HIF1α was primarily expressed in tumor-associated macrophages (TAM), whereas HIF2α and HAF were mainly expressed in tumor cells [ 74 ]. TAM-associated HIF1α was significantly associated with high tumor grade and increased metastasis and was independently associated with decreased overall survival [ 74 ].…”
Section: Hif1α and Hif2αmentioning
confidence: 99%